2004
DOI: 10.1089/ten.2004.10.1641
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Acellular Nerve Graft Is Immunologically Tolerated and Supports Regeneration

Abstract: The long-term goal of our research is to engineer an acellular nerve graft for clinical nerve repair and for use as a model system with which to study nerve-extracellular matrix interactions during nerve regeneration. To develop this model acellular nerve graft we (1) examined the effects of detergents on peripheral nerve tissue, and (2) used that knowledge to create a nerve graft devoid of cells with a well-preserved extracellular matrix. Using histochemistry and Western analysis, the impact of each detergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
192
0
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 306 publications
(220 citation statements)
references
References 34 publications
5
192
0
18
Order By: Relevance
“…The most commonly utilised methods for decellularisation of nerve tissue include cold preservation; (Evans et al, 1998), thermal (Ide et al, 1998; Gulati, 1988) radiation (Hiles, 1972) and detergent based chemical treatments (Hudson et al, 2004; Sondell et al, 1998). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most commonly utilised methods for decellularisation of nerve tissue include cold preservation; (Evans et al, 1998), thermal (Ide et al, 1998; Gulati, 1988) radiation (Hiles, 1972) and detergent based chemical treatments (Hudson et al, 2004; Sondell et al, 1998). …”
Section: Resultsmentioning
confidence: 99%
“…There have however been reports that the freeze‐thawing process fails to remove the cell debris from the tissue, in addition to fracturing the basal laminae that surround the axons (Hudson et al, 2004). In vivo studies have demonstrated cellular remnants left behind from this process have led to cellular invasion in the form of Schwann cells and macrophages invading the basal lamina to clear away the debris.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations